Technostress Creators and Inhibitors on the Psychological Well-Being Of Tertiary Educators in the State Universities in CALABARZON Region, Philippines - Carlo Emil Manabo (Universidade Estadual de Alagoas, 2024)
This study determined the demographic profile of the tertiary educators, their level of technostress creators and inhibitors, and the level of their psychological well-being. Likewise, the correlation among the said variables were also identified. A descriptive-correlational research design was employed in the study with a total of two hundred thirty-one (231) regular faculty members as participants. Frequency count and percentage, median, and Spearman's Rank-Order correlation were used to analyze the gathered data. Results revealed that most of the participants are in the middle age of their career, female, taking their PhD units, are in the assistant professorial level, have been connected in the university for sixteen years and above, and majority have no ICT related training attended for academic year 2023-2024. Findings also revealed that there was a low level of technostress creators and a high level of technostress inhibitors in the state universities in the region. Furthermore, findings revealed that the tertiary educators have a high level of psychological well-being in all of its aspects. Further, the results showed a significant negative correlation between the level of technostress creators and the level of psychological well-being; and a significant positive correlation between the level of technostress inhibitors and the level of psychological well-being of the tertiary educators. Thus, it only means that to improve the level of psychological well-being of the tertiary educators, the level of technostress creators must be reduced and the level of technostress inhibitors must be strengthened. This will ensure the continuous integration of ICTs in education by the tertiary educators for a technology-driven education in CALABARZON region.